Interstellar tracers of hadronic processes associated with Tev gamma rays from supernova remnants - Mohammadtaher, Safarzadeh (My University, 2010)
In this study the effect of a sudden increase in flux of cosmic rays near a molecular cloud that is close to the W51C supernova remnant is investigated. The cloud is seen by the Fermi LAT observatory to glow in gamma rays with luminosity of 10^36 erg s^-1, which makes it one of the most luminous sources in the galaxy in gamma rays. The gamma rays can have several possible origins but the one that can justify other observations done in different wavelengths and be consistent with them is a hadronic origin in which proton-proton collisions is the cause of the gamma ray productionin GeV regime. I predict two kinds of effects. The low energy section of the cosmic rays that are the main agents to ionize the cloud ahead of the shock front raises the ionization rate up to 3 or 4 orders of magnitude in comparison to galactic mean ionization rate which is about 10^-16s^-1. The raise in ionization rate leads to interesting ion-neutral chemistry in pre-shocked gas. The proper tracers for high ionization rates are those reactive ions that will not be saturated by increase in ionization level and so exhibit a linear relation between their abundance and degree of ionization like OH^+ and CH^+. The high-energy tail of the cosmic ray spectrum will lead to inelastic p-p collisions and is the main cause for the observed gamma rays from W51C. Beside gamma rays, positrons are also produced during these collisions and will make positronium via charge exchange with H2 molecules in the cloud. Of these positrons, only those with kinetic energy less than 1 MeV are thermalized within the cloud and lead to positronium formation. About 10% of the time the positronium is formed in the n=2 excited state and emits Lym α line before annihilation and there is the possibility to detect the line. The flux of this line received on earth is around 6x10^-9 photon m^-2 s^-1 µm^-1 or 7×10^-13 photon m^-2s^-1.
Keywords: Grundläggande vetenskaper; Astronomi; Basic Sciences; Astronomy